Personalized porous tantalum implants crafted via 3D printing: new horizons in complex cervical-thoracic spinal fusion - Chen, Chang; Fan, Huaquan; Chen, Ge; Li, Zhong; Wang, Puquan; Wang, Fuyou (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundComplex interbody fusion remains challenging, while traditional surgical instruments are not suitable for complex spinal deformities. Porous tantalum (Ta) has excellent osteogenic properties, but there is currently a lack of research on its application in cervical thoracic interbody fusion.ObjectiveTo introduce the application of selective electron beam melting (SEBM) 3D printing technology in customized porous Ta vertebral fusion implants and evaluate its mid-term clinical efficacy in complex cervical thoracic fusion surgery. Method: Porous Ta implants were manufactured using SEBM technology. The mechanical properties were optimized and characterized. Three patients who underwent complex cervical and thoracic fusion surgery were prospectively recruited. 3D printing technology is used for preoperative planning and customized implant design. Surgical techniques and postoperative management follow standard procedures, with regular follow-up including clinical and imaging evaluations.ResultPorous Ta implants have satisfactory pore structure and surface characteristics, with mechanical properties. All three surgeries were successful. The operation time is 188–525 min (average 387.7 min), the intraoperative blood loss is 300–1,000 mL (average 695 mL), and the hospitalization time is 21–36 days (average 30.0 days). After an average follow-up of 24.3 months, the patient’s pain symptoms improved significantly and no serious complications occurred.ConclusionThe use of 3D printed personalized porous tantalum implants in complex spinal fusion procedures is feasible and has shown significant benefits. Future research should focus on validating these results through larger cohorts and long-term follow-up to explore the broader application prospects.